Variance analysis for grain number related traits and study of population structure in rice (Oryza sativa) - MOHANTY, N; NAYAK, S K; KUMAR, J; MOHANTY, S; MOLLA, J; BEHERA, L (The Indian Journal of Agricultural Sciences, 2023)
Utilising average data from the rainy (kharif) seasons of 2021 and 2022, the genetic diversity of 188 recombinant inbred lines (RILs) of rice (Oryza sativa L.) was evaluated at the research farm of ICAR-National Rice Research Institute, Cuttack, Odisha. The grain number and associated 10 characteristics' coefficient of phenotypic variability was substantial, with the grain number per panicle having the greatest PCV and GCV. Principal component analysis was used to further identify the relationships and trends among the RILs. The first four primary components (74.58%) fully described the variability of all 10 features. Cultivars were divided into 8 groups based on the characters used to attribute grain number. To analyse genetic differences between RILs at the molecular level, 22 SSR markers were utilised and the PIC value was 0.709. A strong and significant relationship between them was shown by the structural analysis, with spikelet number and spikelet fertility per cent indicating a particularly strong correlation. Between clusters 1 and 3, there was considerable genetic variety, which offers great breeding options.